Preeclampsia Management: Advancements, Guidelines, and Emerging Perspectives: Manajemen Preeklampsia: Kemajuan, Pedoman, dan Perspektif yang Muncul - Zainab Abdlkadhim Aboshnin; Safa Azhar Razzaq; Layla Hammody Hashem (Universitas Muhammadiyah Sidoarjo, 2024)
Chronic elevation in blood pressure during gestation poses a significant risk for maternal mortality, particularly in the United States. Understanding the pathophysiology of preeclampsia, a specific form of gestational hypertension, has led to developments in management strategies aimed at improving outcomes for both mothers and babies. This abstract outlines the underlying mechanisms, international guideline-based management approaches, and newer perspectives in addressing hypertension during pregnancy. The goal is to balance risks and benefits effectively, enhancing the care of pregnant women with hypertension. Highlights: Understanding the pathophysiology of preeclampsia is crucial for effective management. International guidelines provide a framework for optimizing care for pregnant women with hypertension. Emerging perspectives offer insights into potential advancements in treatment strategies. Keywords: Hypertension, Preeclampsia, Eclampsia, Antihypertensive Drugs